2022
DOI: 10.3390/su141911884
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Production from Surplus Electricity Generated by an Autonomous Renewable System: Scenario 2040 on Grand Canary Island, Spain

Abstract: The electrification of final energy uses is a key strategy to reach the desired scenario with zero greenhouse gas emissions. Many of them can be electrified with more or less difficulty, but there is a part that is difficult to electrify at a competitive cost: heavy road transport, maritime and air transport, and some industrial processes are some examples. For this reason, the possibility of using other energy vectors rather than electricity should be explored. Hydrogen can be considered a real alternative, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The optimal solution is the one with the lowest NPC, but other solutions can also be considered based on other criteria, such as lower total installed power, minimization of energy wastages, or a weighted combination of several factors. However, in this case, we follow the common practice of other researchers and select the global optimal solution as the best one [12,13].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The optimal solution is the one with the lowest NPC, but other solutions can also be considered based on other criteria, such as lower total installed power, minimization of energy wastages, or a weighted combination of several factors. However, in this case, we follow the common practice of other researchers and select the global optimal solution as the best one [12,13].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, this consumption represents around 10% of overall consumption, so it could be considered that there is no seasonality. For these reasons, H 2 production has been considered in this study to be uniformly distributed daily between 12 h (8:00 a.m. and 8:00 p.m.), as it has also been suggested previously in similar research studies [13]. However, to account for the inherent variability that exists in end-use processes, a random hourly variability of up to 20% has been implemented.…”
Section: The Balearic Demand and Electric Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 Hydrogen evolution through photocatalytic water splitting is a way that can be considered as a renewable energy source. 6 A study suggested that only 80 minutes of solar radiation on the surface of the Earth is sufficient for the annual energy requirement around the globe. 7 Hence, hydrogen production through photocatalytic water splitting using semiconductors is a promising way of converting the solar radiation into chemical fuels, not only at a large scale but also at a reduced cost.…”
Section: Introductionmentioning
confidence: 99%